O "Enigma Bijagó" : saberes coloniais em disputa no Centro de Estudos da Guiné Portuguesa (1946-1967) - Scholl, Camille Johann (2017)
This work investigates the anthropological discourse built on the Bijago folks by Portuguese Guinea Studies Center’s members over the years that they produced the Portuguese Guiné Cultural Bulletins (1946-1973). The organizing principle of research is the discourse. This focuses on the concepts used by the authors to compose their arguments, that are matriarchy, totemism, animism and fetishism. They are the nucleus of the "bijago enigma" discussed by José Mendes Moreira, Augusto José de Santos Lima, Avelino Teixeira da Mota and Fernando Rogado Quintino within 1946-1947 and 1962-1967.